2016
DOI: 10.3390/molecules21020149
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling Reveals the Effect of Dietary Rubus coreanus Vinegar on Ovariectomy-Induced Osteoporosis in a Rat Model

Abstract: Abstract:The study was aimed at exploring the curative effects of Rubus coreanus (RC) vinegar against postmenopausal osteoporosis by using ovariectomized rats as a model. The investigations were performed in five groups: sham, ovariectomized (OVX) rats without treatment, low-dose RC vinegar (LRV)-treated OVX rats, high-dose RC vinegar (HRV)-treated OVX rats and alendronate (ALEN)-treated OVX rats. The efficacy of RC vinegar was evaluated using physical, biochemical, histological and metabolomic parameters. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 58 publications
2
19
0
1
Order By: Relevance
“…Likewise, the significant increased levels of lysoPCs were also found in Liu’s study [40]. These lysoPCs likely enhanced oxidative stress by generating reactive oxygen species (ROS), the production of which disturbed the balance of the antioxidant–oxidation process, and the associated oxidative stress may lead to extensive bone loss and skeletal fragility [39]. Further, the disturbance of fatty acid metabolism also causes bone loss.…”
Section: Biological and Metabolic Significance Of The Biomarkersmentioning
confidence: 65%
See 2 more Smart Citations
“…Likewise, the significant increased levels of lysoPCs were also found in Liu’s study [40]. These lysoPCs likely enhanced oxidative stress by generating reactive oxygen species (ROS), the production of which disturbed the balance of the antioxidant–oxidation process, and the associated oxidative stress may lead to extensive bone loss and skeletal fragility [39]. Further, the disturbance of fatty acid metabolism also causes bone loss.…”
Section: Biological and Metabolic Significance Of The Biomarkersmentioning
confidence: 65%
“…Lee et al have shown metabolic differences between OVX SD rats and sham rats based on GC/MS spectra of plasma samples through data analysis using principal component analysis (PCA) and partial least squares-discriminate analysis (PLS-DA). Three potential biomarkers were mainly identified as lower concentrations of phenylalanine, tryptophan and butyric acid [39]. Ma et al compared metabolic perturbations, as measured by GC/MS, between OVX SD rats and sham rats.…”
Section: The Biomarkers and Their Potential Values In Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the rats were 13 weeks old at the time of ovariectomy, which is reportedly acceptable for the osteoporosis model [45, 46]. Furthermore, Francisco et al compared the effects of ovariectomy in rats of different ages and found no related differences in bone mineral response [47].…”
Section: Discussionmentioning
confidence: 99%
“…Sprague Dawley rats are a valuable model for the induction of osteoporosis after hormonal depletion via ovariectomy [43,44]. Here, the rats were 13 weeks old at the time of ovariectomy, which is reportedly acceptable for the osteoporosis model [45,46]. Furthermore, Francisco et al compared the effects of ovariectomy in rats of different ages and found no related differences in bone mineral response [47].…”
Section: Discussionmentioning
confidence: 99%